Analysis of changes in fees for the collection and management of municipal waste as regards the efficiency of waste segregation - Malinowski, Mateusz; Łukasiewicz, Maria; Famielec, Stanisław; Nowińska, Karina (Economics and Environment, 2019)
The issue discussed in this paper is related to the correlation between the efficiency of waste segregation and fee rate imposed on residents for generated municipal solid waste, which rate is set and changed by municipal authorities. The main objective of the paper was to analyse the variability of fees for waste collection and management, as well as to analyse changes within this scopeduring the first several years (from 1 July 2013 to 31 December 2016) since the new waste management system was implemented in Poland. The research area included the municipalities of the 1st Waste Management Region in the Silesian Voivodeship. The mean fee sustained by residents of the examined municipalities for the collection and management of mixed waste was PLN 14.1 per person per month; when residents opted for additional selective waste collection, the fee was PLN 7.3 per person per month. During the examined period, the waste collection fee increased in the majority of the municipalities by 34.0%. One third of the municipalities did not change the rate. In those municipalities where the fee increased, the growth of segregation efficiency was hampered. The mean share of the segregated municipal waste stream in the total stream of collected waste reached 22.6%. No significant correlation was observed between the applied fee rate and efficiency of selective waste collection.